Scher and Daniel's Nails Diagnosis, Surgery, Therapy (Springer International Publishing, 2018)
This thoroughly updated 4th Edition of this highly regarded text continues to provide the latest therapeutic and surgical information on nail disease and disorders. It expands and updates all areas of onychology, including the newest in diagnostic techniques for nail diseases, a segment of dermatology that not only proves more difficult than cutaneous disorders but also is an exciting and innovative area on the frontier of skin research. Scher and Daniel's Nails: Diagnosis, Surgery, Therapy provides an update of therapeutic advances to help the resident, practitioner, and related healthcare provider (podiatrist, nurse, primary care physician, and all involved in nail care). A major section is devoted to nail surgery and nail pathology, both of which have been behind compared to other aspects of dermatology. There is also extensive information on the billion dollar nail cosmetics industry, which will bring this text to the attention of all nail technicians (several hundred thousand in the US alone) as well as to cosmeticians and manufacturers.